Association between physical activity and health-related quality of life in children: a cross-sectional study. Issue 1 (December 2016) - Wafa, Sharifah; Shahril, Mohd; Ahmad, Aryati; Zainuddin, Laila; Ismail, Karimah; Aung, Myat; Mohd Yusoff, Noor
Abstract Background Research suggests that physical activity plays a role to improve health related- quality of life (QoL), however studies examining the association between physical activity and HRQOL are limited in the paediatric literature. The aim of this study is to explore the relationship between physical activity and HRQoL among Malaysian children. Methods Participants (n  = 78 normal weight; 78 obese children) aged 9–11 years completed a validated quality of life (QoL) inventory and wore an accelerometer to objectively measure physical activity for 1 week. Results Psychosocial Health domain and Total QoL (allp  < 0.05) were significantly lower for obese compared to normal weight children. Children who spent more time in sedentary behaviour had significantly lower QoL on Psychosocial Health domain and Total QoL except for the Physical Health domain. There was also a strong positive correlation between QoL and moderate-vigorous physical activity (MVPA) indicating that children who are physically active have a better quality of life. Conclusions Physical activity promotion should be emphasised to improve QoL in children.